2022
DOI: 10.2147/tcrm.s371396
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Use of Perampanel in Elderly Asian Patients with Epilepsy: Expert Opinion

Abstract: Managing epilepsy in the elderly remains complicated largely due to factors related to aging. In this population, management practices are increasingly shifting towards the use of newer-generation anti-seizure medications (ASMs) as they are generally associated with better tolerability and safety profiles than older ones. Perampanel is a new ASM with broad-spectrum efficacy and a favorable safety profile. However, because of the lack of information and experience in its use, the prescription of perampanel has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In this study, a few transient adverse effects were observed in the patients receiving perampanel, all of which were mild, and none of the patients discontinued perampanel. Previous reports have indicated an increased risk of adverse effects in older patients with perampanel doses exceeding 8 mg, 27 suggesting that the low dosage used in this study (2.14 mg) may have reduced the occurrence of adverse effects. Conversely, careful dose adjustments may lead to stable serum concentrations in patients with epilepsy undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, a few transient adverse effects were observed in the patients receiving perampanel, all of which were mild, and none of the patients discontinued perampanel. Previous reports have indicated an increased risk of adverse effects in older patients with perampanel doses exceeding 8 mg, 27 suggesting that the low dosage used in this study (2.14 mg) may have reduced the occurrence of adverse effects. Conversely, careful dose adjustments may lead to stable serum concentrations in patients with epilepsy undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 52%
“…This trend of better seizure control in elderly Asians with perampanel has also been observed by epilepsy experts across Asia such that an expert opinion article was published in 2022. 23 Regarding tolerability, mean retention time in WRAPPER was 44.5 weeks (SD 1.7, 95% CI 41.2-47.8) comparable to that of PERMIT at 43.2 weeks (95% CI 42.4-43.6). Seizure exacerbation was the most common adverse effect at 35.7% (25/70) at 16 weeks.…”
Section: Discussionmentioning
confidence: 83%
“…This trend of better seizure control in elderly Asians with perampanel has also been observed by epilepsy experts across Asia such that an expert opinion article was published in 2022. 23 …”
Section: Discussionmentioning
confidence: 99%